2018
DOI: 10.3201/eid2406.171612
|View full text |Cite
|
Sign up to set email alerts
|

Human Endophthalmitis Caused By Pseudorabies Virus Infection, China, 2017

Abstract: We report human endophthalmitis caused by pseudorabies virus infection after exposure to sewage on a hog farm in China. High-throughput sequencing and real-time PCR of vitreous humor showed pseudorabies virus sequences. This case showed that pseudorabies virus might infect humans after direct contact with contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 9 publications
3
148
0
Order By: Relevance
“…Pseudorabies virus has a wide host range including human and cattle. It has been reported that a pig farmworker was infected by PRV after exposure to sewage (Ai et al, ). There are also several reports in different countries mentioned human was infected by PRV (Wong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudorabies virus has a wide host range including human and cattle. It has been reported that a pig farmworker was infected by PRV after exposure to sewage (Ai et al, ). There are also several reports in different countries mentioned human was infected by PRV (Wong et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, PCR, known as the gold standard for diagnosis, relies on prior knowledge or assumptions of the type of pathogen causing infection [20]. Furthermore, pathogen-specific PCR assays could not provide enough evidence for the etiological diagnosis of viral CNS infections, since dozens of virus families can cause nervous system infections [22] and a few animal viruses with the capability of crossing the species barriers, such as pseudorabies virus, could infect human being [23,24]. However, NGS technique can allow for the detection of etiological evidence in clinical samples without any prior knowledge of pathogen specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudorabies virus (PRV), a member of Alphaherpesvirinae subfamily within the family Herpesviridae , causes Aujeszky's disease mainly in pigs. Recently, Ai et al reported human endophthalmitis caused by PRV infection upon exposure to sewage on a swine farm of Jiangxi Province of China (Ai et al, ), which raised a public concern of PRV as zoonosis. Here, we report another case of severe encephalitis caused by PRV infection in Hebei Province of China.…”
Section: Dynamic Cerebrospinal Fluid (Csf) Analysis Over the Course Omentioning
confidence: 99%
“…Several suspicious cases of PRV infection in Europe developed weakness, sore throat and mild neurological symptoms (Mravak, Bienzle, Feldmeier, Hampl, & Habermehl, ). The recent case in China reported that the patient infected by PRV developed fever, headache and visual impairment (Ai et al, ). In this case, direct contact of contaminated blood from needle stick injury results in disturbed consciousness, and seizures followed by both severe encephalitis and irreversible visual loss.…”
Section: Dynamic Cerebrospinal Fluid (Csf) Analysis Over the Course Omentioning
confidence: 99%